The Effect of Green Buildings on Employees’ Performance - Parida, Subhadarsini (Curtin University, 2020)
This thesis reports on the evaluation of the impact of green human resource management (Green HRM) on performance outcomes in green office buildings in the contexts of Australia and India. This study conducted a systematic literature review to narrow the scope and sequential explanatory mixed-methods research design for data collection. Results from this study advance existing knowledge on Green HRM by creating a ‘sweet spot’ where green buildings’ physical aspects, human resources and performance overlap.